2017
DOI: 10.25100/socolen.v43i2.5942
|View full text |Cite
|
Sign up to set email alerts
|

Resistencia varietal al ataque por Diatraea spp. (Lepidoptera: Crambidae) en caña de azúcar

Abstract: Los barrenadores del tallo, Diatraea spp., constituyen las plagas más importantes de la caña de azúcar en Colombia. En el país, el proceso de obtención de variedades no involucra la selección con respecto a la resistencia a insectos plaga, pero en la etapa final de selección se evalúa el porcentaje de entrenudos barrenados (intensidad de infestación) y se asigna una calificación de daño relativa al daño promedio obtenido en cada prueba, que luego de al menos tres pruebas da lugar a un promedio de calificación … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…In general, CC 93-3826 and CC 93-3895 have exhibited contrasting responses to insect attacks (proportion of bored internodes) both under field conditions (Echeverri-Rubiano et al 2017) and under uniform infestation, as reported in the present study. Studies using controlled infestation, such as those under screen house and/or laboratory conditions, enable homogeneous pest populations per experimental unit (i.e., plants), thus enhancing precision in assessing the impact of genotypes on borer biology, as well as in reducing the prevalence of variables affecting survival such as harsh weather, cannibalism, parasitism, predation, and disease (Rodríguez-Del-Bosque et al 1989, Knutson and Gilstrap 1990).…”
Section: Discussionsupporting
confidence: 75%
See 4 more Smart Citations
“…In general, CC 93-3826 and CC 93-3895 have exhibited contrasting responses to insect attacks (proportion of bored internodes) both under field conditions (Echeverri-Rubiano et al 2017) and under uniform infestation, as reported in the present study. Studies using controlled infestation, such as those under screen house and/or laboratory conditions, enable homogeneous pest populations per experimental unit (i.e., plants), thus enhancing precision in assessing the impact of genotypes on borer biology, as well as in reducing the prevalence of variables affecting survival such as harsh weather, cannibalism, parasitism, predation, and disease (Rodríguez-Del-Bosque et al 1989, Knutson and Gilstrap 1990).…”
Section: Discussionsupporting
confidence: 75%
“…The applicability of our results from screen house experiments to commercial sugarcane production fields is reinforced by the findings of Echeverri-Rubiano et al (2017), as the authors also found more pest injury on CC 93-3826 (susceptible) in comparison to other varieties, including CC 93-3895 (resistant), on regional trials in three different locations in the Cauca River Valley (CRV) of Colombia. Additionally, an increase in pest injury has been observed in association with an increase in susceptible cultivars plantings in the CRV region (Echeverri-Rubiano et al 2018).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations